Endoscopic hemostasis of an active hypopharyngeal hemorrhage via gel immersion endoscopy. Issue 6 (26th July 2022) - Sugawara, Noriaki; Iwatsubo, Taro; Takeuchi, Toshihisa
Abstract : Watch a video of this article.